The option for the poor in Christian theology - Groody, Daniel G., 1964- (University of Notre Dame Press, 2007)
This volume draws on the thought of leading international scholars and explores how the Christian tradition can help us understand the theological foundations for the option for the poor. The central focus of the book revolves around the question, How can one live a Christian life in a world of destitution? The contributors are concerned not only with a social, economic, or political understanding of poverty but above all with the option for the poor as a theological concept.